Integrating a Set of Contract Checking Tools into Visual Studio - Fahndrich, Manuel; Barnett, Mike; Leijen, Daan; Logozzo, Francesco (Proceedings, Proceedings of the 2012 Second International Workshop on Developing Tools as Plug-ins (TOPI 2012), 2012)
Integrating tools and extensions into existing languages, compilers, debuggers, and IDEs can be difficult, workintensive, and often results in a one-off integration. In this paper, we report on our experience of building and integrating the CodeContract tool set into an existing programming environment. The CodeContract tools enable 1) authoring of contracts (preconditions, postconditions, and object invariants),Instrumenting contract checks into code, 3) statically checking code against contracts, and 4) visualizing contracts and results. We identify three characteristics of our integration that allowed us to reuse existing compilers and IDEs, increase the reach of our tools to multiple languages and target platforms, and maintain the tools over three consecutive versions of C# and Visual Studio with little effort. These principles are 1) use source embedding for new language features, 2) use target analysis and rewriting, and 3) use generic plug-ins to isolate tools from the IDE.